Broadleaf weed control with abrasive grit during raspberry establishment. (30th December 2020) - Forcella, Frank; Poppe, Steven; Tepe, Emily; Hoover, Emily
Abstract: Growers desire more techniques to control weeds in horticultural crops that are grown organically and consumed directly, such as red raspberry. Abrasive grit emited via high air pressure is a new method for controlling weeds. Grit derived from corn cobs was examined for its efficacy during the year of raspberry establishment for 2 to 3 years at three sites (seven site-years) and compared with efficacy of hand-weeding as well as no weed control. Grit was applied once or twice weekly after raspberry transplantation in spring until weed emergence ceased in mid to late July. Weeds and raspberry growth were assessed in August. Grit was effective in controlling broadleaf weeds, averaging 94% control across site-years, but control of grass weeds was less than 10%. Total weed (broadleaf plus grass) control across site-years ranged from 51% to 96% and averaged 78%. Raspberry cane growth was affected by weeds, and grit-weeding at least partially alleviated these effects. Thus, abrasive grit allows growers to manage broadleaf weeds effectively without herbicides or soil tillage. However, additional research is needed to determine the correct amounts and timing of grit applications, as well as more efficacious types of grit, to control grass weeds.